Taking aim: Progress on setting nutrition targets - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
THROUGH THE WORLD HEALTH ASSEMBLY (WHA), COUNTRIES HAVE SIGNED ONTO GLOBAL NUTRITION TARGETS, AND AS CHAPTER 2 SHOWS, ONE WAY to track countries’ progress is to apply these global targets to the national level. Yet targets that countries set for themselves are likely to be more effective tools for promoting accountability. By definition, these self-generated targets have greater government buy-in and ownership than those set from outside the country. And these targets are most useful for accountability when they are SMART (that is, specific, measurable, achievable, relevant, and time bound).